Does work motivation and work discipline affect employee performance during Covid-19? - Dwi Orbaningsih; Ervan Dwi Priyanto; Gendut Budi Wahyono; S.B.P. Handhajani (International Ecsis Association, 2022)
The covid 19 pandemic has changed people's behavior. Social and physical distancing policies are government policies that have changed employees' work environment from the office to the home environment. Meanwhile, human resource management is needed to maintain and improve the performance of employee (State civil apparatus or ASN). Therefore, this study examines the influence of work motivation and work discipline moderated by the work.environment.on.the performance of the employee (ASN). The research site was Badan Keuangan dan Aset Daerah Pemerintah Kota Batu. This research used a quantitative method with explanatory research. The population in.this.study.was all State civil apparatus (ASN) of the Badan Keuangan dan Aset Daerah Pemerintah Kota Batu as many as 61 respondents. This study found that work motivation influences the performance of the employee (ASN), and work discipline also affects on ASN performance. In addition, the work environment is a variable that moderates dependent variables towards the performance of the ASN. This research implies that the work environment is critical to be considered as a strategy to maintain ASN motivation and work discipline.